The Relationship between the Level of Nutritional Knowledge, Parenting Patterns and Sanitation with the Incidence of Stunting in Toddlers Age 2-5 Years in Sukoharjo Village, Wilangan District, Nganjuk Regency - Nur Khasanah, Lutfianti Dwi (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Children under five who are stunted are too small for their age due to a persistent malnutrition-related failure to thrive. In Sukoharjo Village, Wilangan District, Nganjuk Regency, the percentage of instances of stunting was 23.3%. The purpose of this study is to ascertain the correlation between the occurrence of stunting in children ages 2 to 5 in Sukoharjo Village, Wilangan District, Nganjuk Regency, and the degree of nutritional awareness, parenting styles, and cleanliness. This study uses a cross-sectional design and is correlational in nature. Eighty moms of toddlers answered the survey. A nutritional knowledge exam was used to collect data on nutritional knowledge; a questionnaire was used to collect data on eating patterns; and a questionnaire was used to collect data on cleanliness. The TB/U index is used to determine if toddlers are stunted or in normal condition. The chi square test is used in the variable relationship analysis method. The study’s findings indicate that: (1) nutritional knowledge and stunting incidence are significantly correlated; (2) parenting styles and stunting incidence are significantly correlated; and (3) sanitation and stunting incidence among toddlers in the village are significantly correlated. Wilangan District, Sukoharjo, Nganjuk Regency.